Clinical Utility of Respiratory Scores at Admission for Estimating the Definitive Microbiological Diagnosis in Lower Respiratory Tract Infections in Infants - And Demir MD, PhD, MBA; Nihal Özdemir Karadas MD; Ulas Karadas MD (SAGE Publishing, 2022)
We aimed at determining the clinical utility of respiratory scores and the durations of wheezing or respiratory distress during hospitalization in infants with lower respiratory tract infections (LRTI) at admission for estimating the definitive microbiological diagnosis. We obtained data from a study population of 201 patients, 79 girls and 122 boys. There was a significant divide in the causative agents of LRTI among patients younger and older than 6 months of age ( P = .002), and significantly different respiratory score findings were determined in infants with viral LRTI: a low respiratory score in a younger-than-6 month infant suggests Adenovirus as the causative agent and a high respiratory score suggests Parainfluenza 1 or 2; as for infants of 6 months of age or older, a low respiratory score indicates Influenza A or B or a mixed infection, whereas a high respiratory score is likely an indication of Parainfluenza 3 or RSV.